Interrogativity : a colloquium on the grammar, typology and pragmatics of questions in seven diverse languages, Cleveland, Ohio, October 5th 1981-May 3rd 1982. - Chisholm, William (Topical studies in language., 1984)
This is a comparative study on the subject of interrogativity, presenting broad and narrow attributes on this subject in diverse languages: Russian, Mandarin, Georgian, Bengali, Bantu, Japanese, West Greenlandic and Ute. Each contribution presents, first the basic facts about the language in question, its more recent provenience, facts about numbers of speakers, writing systems, and related areal and sociolinguistic points. An overview of the typological hallmarks follows together with a sketch of the grammar broadly construed. Finally, the grammar of interrogativity is described and the seman.